Development and evaluation of a supersized aluminum flat plate heat pipe for natural cooling of high power telecommunication equipment. (5th February 2021) - Li, Ji; Li, Xingping; Zhou, Guohui; Liu, Yang
Graphical abstract: Highlights: A super-sized aluminum-based flat plate heat pipe was developed. The aluminum flat heat pipe can work well in vertical or horizontal position; The highest thermal conductivity of the flat heat pipe is about 11500 W/m⋅K; The heat sink thermal resistance is reduced by more than 30% under natural convection. Abstract: The large-sized heat spreader plays an important role in strengthening the heat dissipation of outdoor telecommunication equipment. If simply enlarging the traditional vapor chamber structure, it faces the shortcomings of complex structure, difficulty in manufacturing, and low mechanical strength. In this paper, guided by a theoretical analysis, a super-large aluminum-based flat heat pipe (FHP) heat spreader with the overall size of 420mm × 210 mm × 6.3 mm was developed and systematically studied under natural convection condition. The results show that the proposed aluminum FHP can effectively manage thermal loads up to 80 W in the vertical gravity-favorable direction with the heat source temperature below 78.9 °C, which is much lower than that of an aluminum plate with the same geometric size. At the same time, the proposed flat heat pipe was combined with a finned heat sink to test the heat dissipation capability of the module under natural convection condition. The FHP heat sink module can effectively dissipate 150 W of heating power with a local heat flux of 24 W/cm 2 when placed vertically before the substrate temperature of the module approaches to 80 °C, and reduce the temperature of the heat source by 20 °C compared to a traditional aluminum finned heat sink module with the same geometries. The proposed aluminum FHP provides a promising thermal management solution for high-power telecommunication equipment, and exhibits high potential for cooling high power laser, power batteries, and LED lamps, etc.